Flatfish monophyly refereed by the relationship of Psettodes in Carangimorphariae - Wei Shi; Shixi Chen; Xiaoyu Kong; Lizhen Si; Li Gong; Yanchun Zhang; Hui Yu (BMC Genomics, 2018)
Abstract Background The monophyly of flatfishes has not been supported in many molecular phylogenetic studies. The monophyly of Pleuronectoidei, which comprises all but one family of flatfishes, is broadly supported. However, the Psettodoidei, comprising the single family Psettodidae, is often found to be most closely related to other carangimorphs based on substantial sequencing efforts and diversely analytical methods. In this study, we examined why this particular result is often obtained. Results The mitogenomes of five flatfishes were determined. Select mitogenomes of representative carangimorph species were further employed for phylogenetic and molecular clock analyses. Our phylogenetic results do not fully support Psettodes as a sister group to pleuronectoids or other carangimorphs. And results also supported the evidence of long-branch attraction between Psettodes and the adjacent clades. Two chronograms, derived from Bayesian relaxed-clock methods, suggest that over a short period in the early Paleocene, a series of important evolutionary events occurred in carangimorphs. Conclusion Based on insights provided by the molecular clock, we propose the following evolutionary explanation for the difficulty in determining the phylogenetic position of Psettodes: The initial diversification of Psettodes was very close in time to the initial diversification of carangimorphs, and the primary diversification time of pleuronectoids, the other suborder of flatfishes, occurred later than that of some percomorph taxa. Additionally, the clade of Psettodes is long and naked branch, which supports the uncertainty of its phylogenetic placement. Finally, we confirmed the monophyly of flatfishes, which was accepted by most ichthyologists.